Decreased NURR1 and PITX3 gene expression in Chinese patients with Parkinson's disease - Liu, H.; Wei, L.; Tao, Q.; Deng, H.; Ming, M.; Xu, P.; Le, W. (European journal of neurology, 2012)
Background and purpose:  The preferential degeneration of midbrain dopaminergic (mDA) neurons in the substantia nigra pars compacta is the pathological hallmark in Parkinson’s disease (PD). The transcription factors NURR1 and PITX3 have been shown to play a crucial role in the maturation and survival of mDA neurons, and both of them were potential susceptibility genes for PD. Methods:  To determine whether NURR1 and PITX3 gene expression are altered in Chinese patients with PD, we measured their gene expression in human peripheral blood lymphocytes (PBL) in 255 patients with PD and 211 age‐ and gender‐matched healthy controls by quantitative real‐time PCR technique. Results:  We found that both NURR1 and PITX3 gene expression in PBL were significantly decreased in patients with PD as compared with controls (P < 0.0001). Lower levels of NURR1 and PITX3 gene expression were significantly associated with the increased risk for PD in male and older subjects, respectively. Conclusions:  Our results provide useful information that the NURR1 and PITX3 gene expression is decreased in the PBL of Chinese patients with PD, indicating their possible systemic involvement in PD.